Effects of different temperature and duration during cold storage and transportation on physico-chemical properties, microbial safety and sensory attributes acceptability of broiler chicken breast - Hayat, Muhammad Nizam (2019)
Temperature plays an important role in meat processing. Observations in poultry processing plants have shown a serious deviation in processing temperature compared to the recommended temperature. Furthermore, there is still a paucity of evidence on the effects of temperature on meat quality and microbial population. The aim of the first experiment was to compare the effects of different temperature and duration during storage on physico-chemical properties and microbial safety of broiler chicken breast. 80 birds were slaughtered and processed following which, the packed boneless breast (PBB) (each bird was to provide 2 breast muscle samples; Left Breast & Right Breast) was divided into 4 groups, each consisted of 40 PBB. Each group was subsequently assigned to storage either at 4°C, -10°C, -18°C or -40°C, for 24 h before 20 PBB samples from each group were transported to laboratory for instrumental meat quality and microbiological analysis. The remaining 20 PBB from each storage temperature were stored for 72 h before transported for analysis. Results have shown that there were significant increases in drip loss and cooking loss as the storage temperature decreases. Similarly, storage duration significantly affected cooking loss, of which, samples stored for 72 h exhibit higher cooking loss compared to those stored for 24 h. For color, significant differences were only observed in lightness (L*) and redness (a*) values. Longer length of storage had significantly improved tenderness whereby, samples that have been stored for a shorter duration presented higher pH values. Populations of coliform and Salmonella decreased significantly with decreasing temperature and increasing storage duration. The second experiment was conducted to determine the influence of temperature and duration of transportation on physico-chemical properties and microbial safety of broiler chicken breast. 60 birds were slaughtered and processed as in the first experiment. During storage, all 120 PBB were stored in -18°C for 24 h before subsequently assigned to transportation temperature either at 4°C, 10°C or 15°C. Sixty of the PBB that were loaded into the cold truck with different temperatures were transported within 1 h, while the remaining 60 were transported within 5 h of traveling time. Different transportation temperature has a significant effect on coliform and Salmonella population without affecting drip loss, cooking loss, lightness (L*), redness (a*), yellowness (b*), pH and tenderness. Transportation duration have significantly affected lightness (L*), redness (a*), yellowness (b*), pH, coliform and Salmonella population of broiler chicken breast. For the third experiment, 210 birds were slaughtered and processed. Immediately after packaging, PBB were divided into two groups, with each consisted of 240 PBB and 180 PBB. The first 240 PBB followed the same procedure as in the first experiment, while the other 180 PBB followed the procedure as in the second experiment. The third experiment provided results related to sensory attributes acceptability of broiler chicken breast that have been stored and transported in different temperature and duration via consumer acceptance survey and sensory evaluation test. For chicken subjected to different storage temperature and duration, samples that were assigned at 4°C and -10°C exhibit better color and aroma score. However, those subjected to -18°C and -40°C storage, were of better scores in terms of tenderness and juiciness. For overall acceptance, consumers prefer chickens which were stored at 4°C for 24 h. As for chicken meats transported at different temperatures and travel durations, samples transported at higher temperature recorded higher scores in aroma, tenderness and juiciness. Similar to storage duration, transportation duration has limited effects on sensory characteristics. Meanwhile, the overall acceptance score of chicken meat transported at different temperatures and durations suggest that consumer prefer chicken meat transported at 10°C for 1 h.